Comparative nutrient utilization efficiency on diets containing combined fruit wastes in view of browser/grazer dichotomy in Ethiopian settings: Woyito-Guji bucks versus Doyo-Gena rams - Mitiku Yohannes; Yisehak Kechero; Yilkal Tadele (Cogent Food & Agriculture)
The use of agricultural and food industry waste as animal feed is considered as best option to fill feed shortage gap and efficient utilization of available resources within food-feed production circularity. The aim of this study was to compare the effectiveness of combined fruit waste meal utilization between Woyito-Guji bucks’ vs. Doyo-Gena rams in a 2 × 4 randomized crossover design with two species, four diets and four periods. The treatments were grass hay with 0% fruit waste (FW) + 100% concentrate mix (CM) (T1), 25% FW + 75% CM (T2), 50% FW + 50% CM (T3) and 75% FW + 25% CM (T4). Regardless of species variation, T1, T2 and T3 had comparable (p > 0.05) body weight gain and feed conversion efficiency values higher (p < 0.05) than that of T4. However, daily nutrient intake measurements of all prepared diets in this particular study shown that Doyo-Gena lambs score higher values (p < 0.05) than that of Woyito-Guji goats in all treatment groups. The nutrient digestibility values for organic matter (OM) and dry matter (DM) scored similarly but that of Crude Protein (CP), Neutral Detergent Fiber (NDF), Acid detergent fiber (ADF) and Ash scored higher (p < 0.05) for Woyito-Guji bucks as compared to Doyo-Gena rams. As a result, similar values for daily body weight gain and feed conversion efficiency were recorded in spite of feed intake variation between species. In general, both species had an improvement in nutrient intake, digestion and performance when fruit wastes were added as an alternative feed, although sheep experienced the greatest improvement.